Thematic Evolution of The Creative Economy in Scientific Publications: A Bibliometric Study (Sustainable Development Insights, 2026)
This study examines the thematic evolution of creative economy research through a bibliometric analysis of scientific publications. Using data retrieved from a major academic database and analyzed with bibliometric mapping tools, the study identifies the intellectual structure, key themes, and emerging trends within the field. The findings reveal that the literature is anchored around core concepts such as creative economy, creative industries, innovation, and economic development, reflecting a strong integration with knowledge-based and innovation-driven perspectives. Over time, the thematic focus has shifted from cultural policy and urban development toward digital transformation, with increasing attention to topics such as the digital economy, artificial intelligence, and platform-based business models. The results also highlight the growing importance of ecosystem thinking, where the creative economy is understood as a system of interconnected actors and value creation processes. This study contributes by providing a comprehensive mapping of the field’s development and offering insights into future research directions, particularly in relation to digitalization and interdisciplinary integration within the creative economy.
Keywords: Creative Economy; Creative Industries; Innovation; Bibliometric Analysis; VOSViewer